Agricultural Land Values Increase: 2003 Survey Results - John E. Reynolds (EDIS)
The 2003 Florida Land Value Survey results indicate that the value of agricultural land increased in all regions of the state during the past year. Survey respondents indicated that the increases in the value of agricultural lands were primarily due to a strong nonagricultural demand for land. The value of citrus land increased after declines for the past two years. Agricultural land values vary by the type of land use and geographic area. This is EDIS document FE439, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published November 2003.